Mechanisms for Cellulose-reactive Polyvinylamine-graft-TEMPO Adhesive - Liu, Jieyi (My University, 2012)
Weak wet strength of paper is one of the major challenges limiting the increase use of paper products. It is difficult to form strong adhesive joints between hydrophilic wet cellulose surfaces. Previous research disclosed an approach using polyvinylamine (PVAm) with grafted TEMPO for oxidation of cellulose to improve wet cellulose adhesion. The object of this research is to further develop new and more eco-friendly approaches to induce adhesion between wet cellulose surfaces. PVAm-graft-TEMPOs (PVAm-TEMPO) with various TEMPO grafting extents were prepared and characterized by electron paramagnetic resonance (EPR) and conductometric titration. The stability studies of fully hydrolysed PVAm in sodium hypochlorite (NaClO) environment were conducted. PVAm can be oxidized and degraded by NaClO in alkaline solution. Furthermore, PVAm-TEMPO was applied into the TEMPO/laccase/O2 oxidation of cellulose. Increased wet adhesion between cellulose surfaces were achieved with this enzyme catalyzed approach and the mechanism of this approach was investigated. PVAm-TEMPO and laccase works together as mediators catalyzing the oxidation of primary alcohol groups on cellulose into aldehyde groups that react to form covalent bonds with primary amines on PVAm. However, cationic PVAm-TEMPO and anionic laccase can form complexes during the oxidation process. Grafted TEMPO in enzyme catalyzed approach offers three significant advantages over small molecule TEMPO (free TEMPO). First, as PVAm has high molecular weight, the oxidation of porous fibers is restricted to the exterior surfaces only, which avoids the excessive oxidation of interior surfaces and prevents from weakening the mechanical property of fibers. Second, TEMPO is concentrated on cellulose surfaces by tethered it to PVAm, compared with water-soluble free TEMPO. Thus the total dose of TEMPO required to oxidize fibers by PVAm
Keywords: PVAm; TEMPO; laccase; cellulose; wet adhesion; adhesive; Chemical Engineering; Chemical Engineering